A Multicomponent Educational and Rehabilitation Approach in Optimizing Outcomes During the Poststroke Subacute Phase - Glinac, Alma; Sinanović, Osman (Acta medica Lituanica, 2024)
Background: Poststroke patients often experience cognitive impairments, motor weakness, and difficulties in daily activities. A multicomponent educational-rehabilitation approach offers a holistic treatment by integrating cognitive and motor training with relaxation, adaptive skills training, and motivational components. Despite its potential benefits, there is limited evidence supporting its effectiveness during the subacute stroke phase. This study evaluates the impact of this approach on cognitive functions, upper extremity motor skills, and daily activity independence during the subacute phase.Materials and Methods: In a prospective, randomized clinical trial, 40 patients participated in a 20-session multicomponent educational-rehabilitation program consisting of 45-minute sessions, five days a week. This program combined cognitive and motor training with additional components such as relaxation and patient education. The control group (N=30) received standard physical therapy, including electrotherapy and speech therapy as needed. Assessments were conducted at admission, after the final session for the experimental group, and one month later for the control group.Results: The experimental group demonstrated significantly greater improvements in cognitive abilities, upper extremity functionality, and daily activity independence compared to the control group (p < 0.001).Conclusion: The multicomponent educational-rehabilitation approach significantly enhances cognitive function, motor skills, and daily activity independence during the subacute phase of stroke recovery. These findings suggest that this approach offers superior recovery outcomes compared to standard care, warranting further investigation into its long-term effects.